Development of English Communication Skills to Enhance Confidence and Quality of Service for Taxi Drivers in the Bangkok Metropolitan Region - Kamput, Thayawadee (Rajapark Journal, 2022)
The purposes of this study were: 1) to analyse the problem conditions and the need to develop the English speaking skills of the taxi drivers in the Bangkok metropolitan region; 2) to develop English speaking skills for the communication of the taxi drivers; and 3) to enhance the taxi drivers’ English communication and confidence in order to increase the quality of service. The sample covered 385 taxi drivers, obtained by convenience sampling. The research instruments were the questionnaire, the conversation exercise, and the one group pre-test post-test design. The data was analysed using the descriptive statistics, percentage, mean, standard deviation, and a paired sample t-test to compare the score of English speaking ability before and after training. The results of the study revealed that 1. The problem conditions of the taxi drivers were at a high level. The desire to develop English speaking skills was at a mid-level; 2. The score of English speaking after training was higher. The outcomes of the training participants between before and after training were statistically significant at 0.01 level; and 3. Taxi drivers’ enhancement of English communication skills and confidence for increasing the quality of service was at the high level of the whole.